PENGEMBANGAN ENSIKLOPEDIA BERBASIS AUGMENTED REALITY PADA MATERI BANGUN RUANG DI KELAS V SD NEGERI 20 PULUBALA - Srisusanty; Pulukadang, Wiwi Triyanty; Marshanawiah, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Srisusanty, 2024. Development of an Augmented Reality (AR) Based Encyclopedia on Geometry Materials in Grade V of SD Negeri 20 Pulubala. Undergraduate Thesis. Departement of Elementary Teacher Education, Faculty of Education, Universitas Negeri Gorontalo. The Principal Supervisor is DR. Wiwy Triyanty Pulukadang, S.Pd., M.Pd and the Co-Supervisor is Andi Marshanawiah, S.Pd., M.Pd. This is a development study which used the Thiagarajan method or 4D development (Design, Define, Development, and Dissiminate). This study examined how the development of learning media with an augmented reality (AR)-based encyclopedia in geometry material in grade V of SD Negeri 20 Pulubala. This research aimed to develop learning media with augmented reality (AR)-based encyclopedias in grade V of SD Negeri 20 Pulubala. The subjects in this study were teachers and students of grade V of SD Negeri 20 Pulubala. This study applied mixed methods: quantitative analysis to determine validation, teacher and student assessment, and qualitative data analysis to discover the results of interviews. This research finding was limited to a limited trial stage. Based on the result of validation by several experst, teacher responses, and product trials, it was found that the average score was 91,26% with the criteria of “very feasibel”. Therefore, the augmented reality (AR)-based encyclopedia developed was very feasible to be used as a medium and learning resource in teaching and learning activites and can be continued at the next stage.